Carbonate chemistry of the Weddell Sea - Chen, Chen-Tung Arthur; United States. Dept. of Energy. Office of Basic Energy Sciences. Carbon Dioxide Research Division (Washington, DC : The Dept., 1984)
Mode of access: Internet.